Trust no one [compact disc, unabridged] - Park, Linda Sue (39 clues. Cahills vs. Vespers, 2012)
When seven members of their family were kidnapped, thirteen-year-old Dan Cahill and his older sister, Amy, got ready for the fight of their lives. But their enemy, a terrifying group known as the Vespers, remained frustratingly elusive. They stay in the shadows, picking off Cahills one by one.